Extraosseous vertebral body haemangioma - Kara O'Donnell; Gerald Quan; Anthony Upton (Interdisciplinary Neurosurgery, 2018)
Vertebral body haemangioma (VBH) is a common incidental finding on imaging, occurring in at least 10% of the population. Typical VBH are comprised of endothelial lined vessels and sinuses between vertical longitudinal bony trabeculae. Occasionally these lesions will demonstrate extraosseous extension resulting in cord or nerve root compression and require active management. Accurate, timely diagnosis is critical particularly given the increased risk of haemorrhage compared with other lesions that occur in this location. These lesions can be rapidly progressive or complicated by a pathological fracture and if diagnosis and treatment is delayed permanent paralysis may result. Both magnetic resonance imaging (MRI) and computed tomography (CT) have independent roles to play in diagnosis, assessment of local complications and preoperative planning to reduce morbidity and mortality. Extraosseous VBH are more likely to have atypical features on MRI, and in some cases CT will be crucial for diagnosis. An accurate preoperative diagnosis will allow for preoparative angiography in selected cases to both aid surgical planning and for preoperative angioembolisation. Keywords: Extra osseous haemangioma, Vertebral body, Magnetic resonance imaging, Cord compression, Myelomalacia, Endothelial cells